A NUMERICAL STUDY OF SPRAY CHARACTERISTICS OF A PRESSURE SWIRL ATOMIZER - T. SREELAKSHMI, ,; Dr N CHIKKANNA, (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper deals with the numerical analysis of 2d model of aPressure Swirl Atomizer, which is developed to study the spray characteristics of atomizer, the flow parameters are SMD, aircore diameterand spray cone angle. The variation in nozzle diametersare 1.5m, 2m and 2.5m usingfuel is jet A and methodology affect flow over the atomizer. Results of CFD simulation indicated the optimum nozzle diameter of the atomizer, methodology required to have uniform flow and Spray characteristics within the atomizer. It also proved that CFD is a convenient tool for designing and optimizing the flow over the atomizer.